THE CORRELATION BETWEEN STUDENTS' LEARNING MOTIVATION AND THEIR ABILITY IN READING COMPREHENSION - Suhaimi; Huda, Zulman (GoAcademica CRP, 2026)
This research investigated the correlation between students' learning motivation and their ability in reading comprehension at eighth grade of MTsN 4 Kerinci. The study employed a quantitative method with correlational technique involving 22 students selected through purposive sampling from a population of 62 students. Data collection utilized questionnaires assessed by Likert scale rating to measure students' learning motivation and multiple choice reading tests measured by H. Douglas Brown's rubric to assess reading comprehension ability. The findings revealed a positive correlation between the two variables with rxy value of 0.721 which was greater than rtable at 5 percent significance level of 0.423, indicating that 52.19 percent of reading ability was influenced by learning motivation. Statistical analysis using SPSS 23.00 showed that t-count value of 12.146 exceeded t-table value of 1.713 with significance level of 0.625 which was less than 0.05, confirming that the alternative hypothesis was accepted. The study concluded that there was a significant positive correlation between students' learning motivation and their reading comprehension ability, suggesting that higher motivation contributes to better reading performance among eighth grade students at MTsN 4 Kerinci.